Writing as teacher education - Cosimo Laneve (Instituto Federal de São Paulo, 2016)
<span style="line-height: 115%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This paper is inviting the teacher to describe everyday teaching. The teacher’s point of view is used to investigate activities that evolve through interaction with existing conditions and the adjustments teachers successfully adopt. Writing is best research tool for investigating experience: you can attribute strong heuristic capabilities to the kind of writing that enables actions to be woven together